Strange bedfellows : how late-night comedy turns democracy into a joke - Peterson, Russell Leslie (Rutgers University Press, 2008)
A significant number of Americans get some of their "news" about politics and national affairs from comedy shows. Is "infotainment" a debasement, or a replacement, for traditional news outlets?